Looking After Minidoka : An American Memoir - Nakadate, Neil (Book collections on Project MUSE., 2013)
During World War II, 110,000 Japanese Americans were removed from their homes and incarcerated by the U.S. government. In Looking After Minidoka the ""internment camp"" years become a prism for understanding three generations of Japanese American life, from immigration to the end of the twentieth century. Nakadate blends history, poetry, rescued memory, and family stories in an American narrative of hope and disappointment, language and education, employment and social standing, prejudice and pain, communal values and personal dreams.